Improvement of Surgical Tactics for Bile Effluvium and Biliary Peritonitis After Cholecystectomy - Arziev Ismoil Alievich; Kurbaniyazov Zafar Babazhanovich; Baratov Manon Bahramovich; Nazarov Zokir Norzhigitovich; Sayinaev Farrukh Karamatovich (Zien Journals, 2022)
The paper analyzes the results of surgical treatment of 5247 patients for various forms of GCB. Bile flow and bile peritonitis in the postoperative period were observed in 93 patients due to "small" injuries (aberrant hepatic-bladder ducts of the gallbladder bed - Lyuschka passages, leakage of the stump of the cystic duct, drainage loss from the choledoch) and damage to the main bile ducts ("large" damage.) Improvement of therapeutic and diagnostic tactics in patients with chole circulation after HE allowed to significantly improve the results of treatment in the main group, where complications in the immediate postoperative period amounted to 8.1%, in the long term - 5.4%, mortality was not observed (in the comparison period - 17.8% and 14.2%, respectively, mortality - 3.6%).
Keywords: cholecystectomy; bile expulsion; biliary peritonitis; surgical tactics